A fungal NRPS-PKS enzyme catalyses the formation of the flavonoid naringenin - Zhang, Hongjiao; Li, Zixin; Zhou, Shuang; Li, Shu-Ming; Ran, Huomiao; Song, Zili; Yu, Tao; Yin, Wen-Bing (Nature communications, 2022)
Biosynthesis of the flavonoid naringenin in plants and bacteria is commonly catalysed by a type III polyketide synthase (PKS) using one p -coumaroyl-CoA and three malonyl-CoA molecules as substrates. Here, we report a fungal non-ribosomal peptide synthetase -polyketide synthase (NRPS-PKS) hybrid FnsA for the naringenin formation. Feeding experiments with isotope-labelled precursors demonstrate that FnsA accepts not only p -coumaric acid ( p -CA), but also p -hydroxybenzoic acid ( p -HBA) as starter units, with three or four malonyl-CoA molecules for elongation, respectively. In vitro assays and MS/MS analysis prove that both p -CA and p -HBA are firstly activated by the adenylation domain of FnsA. Phylogenetic analysis reveals that the PKS portion of FnsA shares high sequence homology with type I PKSs. Refactoring the biosynthetic pathway in yeast with the involvement of fnsA provides an alternative approach for the production of flavonoids such as isorhamnetin and acacetin. Biosynthesis of the flavonoid naringenin in plants and bacteria is commonly catalysed by a type III polyketide synthase (PKS) using one p -coumaroyl-CoA and three malonyl-CoA molecules as substrates. Here, the authors report a fungal non-ribosomal peptide synthetase PKS hybrid FnsA catalysing the formation of naringenin.